Detection of Fenton’s Reagent with Carbamide Peroxide on Heterobasidion insulare Negative Influence and Degradation of Polycyclic Aromatic Hydrocarbons in Contaminated Soil Relocation of Petrochemical Works - Zhang, Yue-Hua; Li, Jia-Lin; Miu, Tian-Lin; Luo, Zhe-Wen (Asian Journal of Chemistry, 2013)
During cultivation of the soil experiment, degradation of polycyclic aromatic hydrocarbons from the migrated petrochemical works contaminated soil by modified Fenton's reaction with carbamide peroxide in laboratory column tests and subsequent aerobic biodegradation of polycyclic aromatic hydrocarbons by native bacteria. The effect of carbamide peroxide addition for 4 and 10 days and saturation of soil with carbamide peroxide was experiment. In both tests the carbamide peroxide dosage was 0.8 g soil. In completely hydrogen peroxide urea saturated soil the degradation of polycyclic aromatic hydrocarbons (44 % within 4 days) by modified Fenton's with carbamide peroxide reaction was uniform over the entire soil column. Compared to partially saturated soil with 25 % in 2 weeks, the effect of the modified Fenton's reaction with carbamide peroxide on the microbial activity in the soil was evaluated based on toxicity experiment with Heterobasidion insulare, checklist of viable and dead cells, microbial extra cellular enzyme activity and oxygen consumption and carbon dioxide production during soil cultivation. As the hydrogen peroxide urea is broken down into oxygen and nitrogen, promote the breeding of indigenous microorganisms. In the tests, the toxicity of column leachate with Heterobasidion insulare increased due to the modified Fenton's reaction with carbamide peroxide. In untreated soil 20-30 % of the polycyclic aromatic hydrocarbons were biodegraded in 8 weeks of cultivation. Cultivation of bio-chemically treated soil slightly increased polycyclic aromatic hydrocarbons-degradation compared to polycyclic aromatic hydrocarbons degradation in untreated soil.